Biological Properties of Streptococcal Cell-Wall Particles III. Dermonecrotic Reaction to Cell-Wall Mucopeptides - Abdulla, Essa M. (1966)
Abdulla, Essa M. (University of North Carolina School of Medicine, Chapel Hill), and John H. Schwab. Biological properties of streptococcal cell-wall particles. III. Dermonecrotic reaction to cell-wall mucopeptides. J. Bacteriol. 91:374–383. 1966.—Intradermal injection of rabbits and guinea pigs with mucopeptide suspensions produced an acute necrotic lesion which reached maximal severity within 24 hr and gradually subsided with scar formation. Necrosis was evident within 4 hr after injection of 100 μg, and an indurated area (10 × 10 mm) was produced with as little as 5.0 μg. Mucopeptides from six bacterial strains were studied. Comparison of cell walls and derived mucopeptides showed that the acute necrotic lesion tended to be more severe as the residual polysaccharide was decreased. Hyperimmunization with mucopeptide reduced the acute reaction, with evidence of immunological specificity. Incubation with lysozyme also modified the reaction in relation to extent of digestion. Toxicity was related to particle size, since extended sonic vibration decreased activity. Histological sections showed intense accumulations of polymorphonuclear leukocytes, along with altered collagen. A chronic nodular lesion appeared about 7 days after injection of the intact cell-wall fragments. In contrast to the acute necrotic reaction, this lesion was rarely produced by the mucopeptide separated from polysaccharide.